Organic-polymeric radial flow biorreactor for liver models - Ramírez-Fernández, O.; Zúñiga-Aguilar, E.; Gómez-Quiroz, L. E.; Gutiérrez-Ruiz, M. C.; Godínez, R. (Revista Mexicana de Ingenieria Biomedica, 2016)
An artificial liver support system is based on the functional hepatocytes being cultured inside a bioreactor; this technique has been used as an effective therapy for treating chronic liver diseases in recent times. This work evaluates different parameters such as cell viability and metabolic function of the hepatocytes when cultured on a hybrid scaffold. The scaffold was built using a polypyrrole plasma coated polymer layer seeded with endothelial matrix for efficient three-dimensional hepatocyte growth within a radial flow bioreactor. The flow rate inside the bioreactor was 7 ml / min. The parts for the bioreactor were either built using food-grade steel and/or glass or the scaffolds comprise a Poly (L-lactic acid)-coated polypyrrole iodine layer or not for HepG2 culture. The results show that the Poly (L-lactic acid)-coated scaffolds increased cell proliferation by 30%, protein production by 16% and albumin secretion by 40% compared with the non-coated scaffold. All experiments were performed thrice and data were analyzed by ANOVA and Tukey statistic models with a p<0.05. The obtained results demonstrated that radial flow bioreactors in conjunction with hybrid scaffolds improve hepatocytes’ physiological and functional properties and could be used as an alternative therapy for patients with liver diseases.